Report on the 25th Polish Conference “Philosophy of Sustainable Development” (Warsaw, 19 January 2022) - Klimska, Agnieszka (Studia Ecologiae et Bioethicae, 2022)
Report summarizes the 25th Polish Scientific Conference in the series “Philosophy of Sustainable Development”, held on January 19, 2022, in Warsaw. Organized by the Department of Ecophilosophy at Cardinal Stefan Wyszynski University, the hybrid-format event brought together interdisciplinary scholars. Plenary lectures and thematic sessions addressed topics such as ecological education, sustainable development, ecopsychology, circular economy, and radical visions of the future. The conference reaffirmed the importance of philosophical reflection on the environmental crisis and the value of interdisciplinary dialogue in seeking sustainable solutions.